Development and Production of Artificial Test Swarf to Examine Wear Behavior of Running Engine Components—Geometrically Derived Designs - Patrick Brag; Volker Piotter; Klaus Plewa; Alexander Klein; Mirko Herzfeldt; Sascha Umbach (Journal of Manufacturing and Materials Processing, 2022)
Subtractive manufacturing processes are usually accompanied by the occurrence of tiny flakes and swarf, which later on cause severe wear and damage, especially in moving components such as rolling or sliding bearings, pistons, etc. However, up until now, such detrimental effects have hardly been investigated. One reason is the lack of a definition of a typical design of debris particle. Therefore, the main goal of the project described in this paper was to elaborate a draft that defines standardized test particles. It had to be evaluated whether test particles could be adequately reproduced and whether they would reveal significant damage potential. Taking into account future mass fabrication, Micro Powder Injection Molding (MicroPIM) was chosen as a production method. Five different 3D designs of geometrically defined test particles were developed. The maximum size of each design was 1167 mm in green state; however, all samples shrank in size during sintering. Specially tailored feedstocks containing 42CrMo4 steel powders were used and the related molding, debinding and sintering procedures were developed. All particle geometries and related mold inserts were developed using a commercial software routine for the layout of runner systems, gate locations and ejector positions. The damage potential of the test particles was evaluated based on trials using journal bearing and shift valve test rigs. Although only a moderate degree of damage potential could be ascertained up until now, it can be expected that the artificial swarf will enable standardized wear test procedures to be developed.